EFIKASI DIRI WARGA BELAJAR PENDIDIKAN KESETARAAN DI SANGGAR KEGIATAN BELAJAR (SKB) KOTA PEKANBARU - Utami, Fitri Nur; Wilson, Wilson; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: This study aims to determine the level of self-efficacy of learningcitizens of equality education in sanggar learning activities (SKB) kota pekanbaru. So the wording of the problem in this study is how high the self-efficacy of learning from equal citizens of equality education in sanggar learning activities (SKB) kota pekanbaru?. This study is expected to provide benefits as a useful input fir citizens learning equality education about the self-efficacy of citizens learning equality educatiion. And can providde information an knowledge in developing further research for thereader. the type of research used in this study is descriptive with a quantitative approach. the Population in this study is the education package on equality package A, package B and package C from the regular class. The population in this study was 62 people who studied. The formula used to determne the sample size is the Slovin (Bambang Prasetyo, 2005). The sample used in this study was 54 study residents with a ritial level of 0,5%. And 20 study residents were piked up from other plae with the same characteristics. Is the examplary tehnique used in this study is adalah Simple Random Sampling sampling is done randomly regardless of the layers that exist in that population. The tool used in this study was a questionnaire with statement about the self-effiay of citizens learning about equality eduation in sanggar learning activities (SKB) kota pekanbaru. With indicators that perform tasks, stengh of onfidane, overome obstacles in the broad field of assignment. Alternative answer and eash answer is weighted, namely: very confident (SY) given a score 5, confident (Y) given a score 4, sure uncertain (KY) given a score 3, uncertain (TY) given a score2, very uncertain (STY) given a score 1.Key Words: Self-Efficacy, Equality Education Teach Citizens